إشكالية عدم الاستقرار السياسي في العراق بعد عام 2003 - عبد الكريم حسين علي (Journal of College of Education, 2020)
the problem of research stems from the need to achieve great national consensus in order to improve the reality of Iraqi society and ensure that it escapes from instability and build a democratic civil state and a civil society dominated by law and social justice away from sectarian quotas and confused policies that have delayed the progress of the political and democratic process towards democracy. The purpose or goal of this research is to show the political reality and demographic change that directly affects the societal nature of the Iraqi street and work to describe and analyze this reality, whether at the level of rulers or at the level of the governed, and to explain the reasons for the lack of understanding between the political parties and the reasons for change and finding Solutions to avoid blockages